Results of total hip artroplasty in our clinic - Altunkılıç, Tarık; Demir, Sukru; Emeli, Adem; Sevimli, Reşit; Yılmaz, Erhan (My University, 2019)
Aim: Patients undergone total hip replacement, performed in our clinic were retrospectively reviewed and discussed in the light of the available literature. The aim of this study was to determine our clinical results.Materials and Methods: The records of patients with total hip arthroplasty performed in our clinic between 2002 and 2008 were evaluated retrospectively. Laboratory values, Harris hip score and complications of these patients were examined.Results: The mean preoperative VAS of the 72 patients with a mean follow-up of 28.9 months was 81.6 preoperatively and the mean VAS was 35.7 in the last control. Harris hip score was 36.7 before the operation and 70.3 in the last control. According to Harris hip score of the patients in the preoperative period, 30 patients were evaluated as moderate and 42 patients as poor. In the postoperative period, 10 patients (13.8%) were excellent, 19 (26.3%) were very good, 30 (41.6%) were good, 6 (8.3%) were moderate, 7 (10%) were poorly rated according to Harris hip score. Biochemical laboratory values measured from venous blood taken at the time of arrival of patients, mean HsCRP 11.67±15.4 mg / l, insulin 14.87±29.53 IU / ml, glucose level 139.11±74.3 mg / dl, CK 426 9±12x8.9 mg / dl and CK-MB were determined as 41.1±46.8 mg / dl.Conclusion: As a result, we think that total hip arthroplasty is still an effective method in advanced hip arthrosis.
Keywords: Genel ve Dahili Tıp